Catechol-O-Methyltransferase Deficiency Leads to Hypersensitivity of the Pressor Response Against Angiotensin II. Issue 6 (June 2017) - Ueki, Norikazu; Kanasaki, Keizo; Kanasaki, Megumi; Takeda, Satoru; Koya, Daisuke
Abstract : Catechol-O-methyltransferase (COMT) metabolizes 2-hydroxyestradiol into 2-methoxyestradiol (2-ME); COMT deficiency has shown to be associated with hypertension in men and preeclampsia, the disease associated with hypersensitivity of pressor response against angiotensin II (Ang II). Here, we found that COMT deficiency could explain the hypersensitivity of pressor response against Ang II in mice because of the lack of 2-ME–dependent suppression of angiotensin II receptor type 1 (AT1R). Male C57BL/6 mice were subjected to COMT inhibitor (COMTi: 25 mg/kg per day) or oil (control) for 4 weeks, with or without low-dose Ang II infusion (ANGII: 70 ng/kg per minute) for the last 3 weeks. The Ang II–infused mice were treated with 2-ME (10 ng/d) or vehicle for the last 1 week. We obtained the following experimental groups: control, ANGII, COMTi, COMTi+ANGII, and COMTi+ANGII+2-ME. We performed similar experiments using the in vivo administration of small interfering RNA of COMT instead of COMTi. Neither ANGII nor COMTi exhibited significant alterations in systolic blood pressure. Compared with ANGII or COMTi, COMTi+ANGII displayed significantly higher systolic blood pressure, albuminuria, and glomerular endotheliosis; 2-ME normalized such alterations. Similar phenotypes were observed in COMT small interfering RNA–treated mice. In the aorta of COMT-deficient mice, AT1R expression was increased; 2-ME suppressed AT1R expression. The 2-ME exhibited peroxisome proliferator–activated receptor γ agonistic activity in vitro and ex vivo plasma from pregnant female mice as well. In vitro, 2-ME suppressed both basal and Ang II–induced AT1R levels in a peroxisome proliferator–activated receptor γ–dependent manner. The 2-ME is relevant to combat COMT deficiency–associated hypertensive disorders via suppression of AT1R by its peroxisome proliferator–activated receptor γ activity. Abstract : Supplemental Digital Content is available in the text.